Adaptation of Community Resilience Scale: Its Association With Fear of Earthquake, Fragility of Happiness, Family Harmony, Family Functioning, and Psychological Adjustment - Korun, Ali Berke; Satici, Seydi Ahmet (SAGE PUBLICATIONS INC, 2026)
Community resilience is vital for psychological adjustment, fostering belonging and collective efficacy during crises. This study adapted the Community Resilience Scale into Turkish and examined its psychometric properties within an ecological and systemic framework. In Study: Part I (N = 640), validity and reliability were supported through confirmatory factor analysis, item response theory, and measurement invariance. In Study: Part II (N = 1,281), structural equation modeling and centrality network analysis showed that family harmony, family functioning, fragility of happiness, and fear of earthquake mediated the relationship between community resilience and psychological adjustment. Findings highlight the central role of family functioning in shaping individual adaptation in collectivist communities. Beyond theoretical and measurement contributions, the study offers implications for social work practice by guiding community-based interventions, strengthening family support systems, and informing resilience-oriented policies that enhance post-crisis well-being.
Keywords: community resilience; fear and crisis; natural disasters; fragility of happiness; family functioning; family harmony; psychological adjustment; HEALTH; Family Studies; Social Work